Significados atribuidos a la cohesión, límites y estrategias de afrontamiento de cuatro progenitoras que tienen una hija o hijo diagnosticado con retraso mental leve (2017)
The present research is the qualitative type and its purpose is to describe the meaning attributed to the cohesion, limits and coping strategies of four progenitors who have a daughter or boy diagnosed with mild mental retardation, allowing the use of influential concepts of systemic model. To obtain better results in the research it was considered pertinent to use the hermeneutic appraach and narrative desing, using as instrument an open interview, which was applied to four progenitors. A